2014
DOI: 10.1530/erc-14-0152
|View full text |Cite
|
Sign up to set email alerts
|

CUX1: a modulator of tumour aggressiveness in pancreatic neuroendocrine neoplasms

Abstract: Pancreatic neuroendocrine neoplasms (PNENs) constitute a rare tumour entity, and prognosis and treatment options depend on tumour-mediating hallmarks such as angiogenesis, proliferation rate and resistance to apoptosis. The molecular pathways that determine the malignant phenotype are still insufficiently understood and this has limited the use of effective combination therapies in the past. In this study, we aimed to characterise the effect of the oncogenic transcription factor Cut homeobox 1 (CUX1) on prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 39 publications
3
19
0
1
Order By: Relevance
“…One study revealed that FGF1 is transcriptionally regulated by CUX1 in the Hs578T human breast cancer cell line and in the Bon-1 human pancreatic neuroendocrine tumour cell line. 15,21 In this study, Figure 5E). Meanwhile, CUX1 acted as a transcriptional activator, and the inhibition of CUX1 notably reduced the transcription and protein expression of FGF1, subsequently inhibiting HGF expression in HUVECs (Figure 5F,G).…”
Section: Dppa-mediated Angiogenesis Inhibitionmentioning
confidence: 49%
See 2 more Smart Citations
“…One study revealed that FGF1 is transcriptionally regulated by CUX1 in the Hs578T human breast cancer cell line and in the Bon-1 human pancreatic neuroendocrine tumour cell line. 15,21 In this study, Figure 5E). Meanwhile, CUX1 acted as a transcriptional activator, and the inhibition of CUX1 notably reduced the transcription and protein expression of FGF1, subsequently inhibiting HGF expression in HUVECs (Figure 5F,G).…”
Section: Dppa-mediated Angiogenesis Inhibitionmentioning
confidence: 49%
“…The study of anti‐angiogenesis often focuses on the regulation of angiogenesis‐pathway gene. The overexpression of CUX1 in pancreatic neuroendocrine neoplasm cells upregulates hypoxia inducible factor‐1α (HIF‐1α) and matrix metalloprotein 9 (MMP9), and the paracrine stimulation of endothelial cells then leads to tumour angiogenesis 15. However, the biochemical role of CUX1 in vascular endothelial cells renains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies, however, did not identify applicable molecular markers for evaluating prognosis of insulinomas. Recently, a study showed that CUX1 mediates progression and angiogenesis in murine neuroendocrine tumors and is associated with malignant behaviors in human insulinomas 37 . Another interesting study revealed that TPD52 protein was associated with survival of patients with insulinomas using proteomic approach 27 .…”
Section: Discussionmentioning
confidence: 99%
“…В настоящее время активно проводятся ИГХ исследования по выявлению биомаркеров злокачественной инсулиномы. Такими кандидатами, по данным некоторых исследований, могут являться: молекула клеточной адгезии (EpCAM) [34], фактор транскрипции CUX1 [35], альдегиддегидрогеназа А1, потенциалзависимый анионселективный канал 1 [36]. В то же время экспрессия опухолевого белка D52 [36] и рецепторов ГПП1 [14] отмечена в большей степени в доброкачественных инсулиномах.…”
Section: патоморфологические исследованияunclassified